2022
DOI: 10.1093/pnasnexus/pgac244
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral nanobody–IL-2 fusions that bind the tumor extracellular matrix suppress solid tumor growth in mice

Abstract: Confining cytokine exposure to the tumors would greatly enhance cancer immunotherapy safety and efficacy. Immunocytokines, cytokines fused to tumor-targeting antibodies, have been developed with this intention, but without significant clinical success to date. A critical limitation is uptake by receptor-expressing cells in the blood, that decreases the dose at the tumor and engenders toxicity. Small-format immunocytokines, constructed with antibody fragments, are hypothesized to improve tumor specificity due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…By fusing wild‐type cytokines to antibodies (referred to as immunocytokines hereafter) directed at tumor‐associated antigens (TAAs), it was hypothesized that systemic exposure and on‐target/off‐tumor toxicity could be reduced. However, we have previously shown that simple immunocytokine targeting does not solve this problem in the context of solid tumors 39,40 . In the case of a systemically administered IL‐2 immunocytokine targeted to the melanoma marker TRP1, Tzeng et al demonstrated that the biodistribution of the fusion protein is entirely governed by cognate cytokine receptor expression patterns 39 .…”
Section: Spatial Programming To Tumor Tissues Via Target Binding—firs...mentioning
confidence: 99%
See 4 more Smart Citations
“…By fusing wild‐type cytokines to antibodies (referred to as immunocytokines hereafter) directed at tumor‐associated antigens (TAAs), it was hypothesized that systemic exposure and on‐target/off‐tumor toxicity could be reduced. However, we have previously shown that simple immunocytokine targeting does not solve this problem in the context of solid tumors 39,40 . In the case of a systemically administered IL‐2 immunocytokine targeted to the melanoma marker TRP1, Tzeng et al demonstrated that the biodistribution of the fusion protein is entirely governed by cognate cytokine receptor expression patterns 39 .…”
Section: Spatial Programming To Tumor Tissues Via Target Binding—firs...mentioning
confidence: 99%
“…Small‐format immunocytokines, such as those designed with nanobody fragments instead of full‐length IgGs, have been proposed to have improved tumor specificity over larger antibody‐based immunocytokines due to their rapid renal clearance 39,40 . However, theoretical analysis of the fundamental rate processes of tumor localization suggests that with few exceptions, this may not be the case 44‐46 .…”
Section: Spatial Programming To Tumor Tissues Via Target Binding—firs...mentioning
confidence: 99%
See 3 more Smart Citations